Asthma, allergy and the Olympics: a 12-year survey in elite athletes. Issue 2 (April 2015) - Bonini, Matteo; Gramiccioni, Claudia; Fioretti, Daniela; Ruckert, Beate; Rinaldi, Monica; Akdis, Cezmi; Todaro, Antonio; Palange, Paolo; Carlsen, Kai-Hakon; Pelliccia, Antonio; Rasi, Guido; Bonini, Sergio
Abstract : Objective: There are no comprehensive surveys relating the reported high prevalence of asthma and allergic diseases in athletes to comorbidities and immune changes associated with intense chronic exercise. This 12-year survey aims to evaluate several clinical, functional and immunological parameters in order to assess features, trend and burden of asthma, allergy, infections and autoimmune diseases, in a large homogeneous population of Olympic athletes. Methods: Six hundred and fifty-nine Italian Olympic athletes were studied through four cross-sectional surveys performed between 2000 and 2012 before the Summer and Winter Olympics. Clinical diagnosis of allergic, autoimmune and infectious diseases was complemented by: skin-prick tests ( n  = 569); pulmonary function tests ( n  = 415); total ( n  = 158) and specific ( n  = 72) serum IgE; serum autoantibodies ( n  = 30), cytokines and growth factors ( n  = 92); flow cytometry ( n  = 135). Results: The prevalence of asthma and/or exercise-induced bronchoconstriction was 14.7%, with a significant increase ( P  = 0.04) from 2000 (11.3%) to 2008 (17.2%). The prevalence of rhinitis, conjunctivitis, skin allergic diseases and anaphylaxis was 26.2%, 20.0%, 14.8% and 1.1%, respectively. Sensitization to inhalant allergens was documented in 49.0% of athletes, being 32.7% in 2000 and 56.5% in 2008 ( P  < 0.0001). Food, drug and venom allergy was present in 7.1%, 5.0% and 2.1% of athletes, respectively. The high prevalence of asthma and allergy was associated with recurrent upper respiratory tract (10.3%) and herpes (18.2%) infections, an abnormal T cell subset profile and a general down-regulation of serum cytokines with a significantly lower IFN-γ/IL-4 ratio. Conclusion: A chronic and intense physical exercise may cause a transient immunodepression with a preferential shift to a Th2 response, associated with abnormalities of the respiratory tract. Abstract : Supplemental Digital Content is available in the text